High‐Performance Ultrapure Green CdSe/CdS Core/Crown Nanoplatelet Light‐Emitting Diodes by Suppressing Nonradiative Energy Transfer. (25th January 2021) - Wen, Zuoliang; Liu, Pai; Ma, Jingrui; Jia, Siqi; Xiao, Xiangtian; Ding, Shihao; Tang, Haodong; Yang, Hongcheng; Zhang, Chaojian; Qu, Xiangwei; Xu, Bing; Wang, Kai; et al.
Abstract: Colloidal nanoplatelets (NPLs) are an emerging semiconductor nanocrystal in the display community due to their ultranarrow emission linewidth. Herein, an ultrapure green emitting nanocrystal light‐emitting diode (LED) based on four‐monolayer CdSe/CdS core/crown NPLs is developed. By applying the nonstacked nanoplates, the nonradiative energy transfer in the NPLs film is successfully suppressed. The nonstacked NPL‐LEDs with pure green emission of 521.5 nm exhibit a low turn‐on voltage of 2.1 V, a maximum luminance of 22 400 cd m −2, a peak external quantum efficiency (EQE) of 2.16%, which is a sixfold enhancement comparing to the stacked NPL‐LED (EQE = 0.34%). This work demonstrates the potential of core/crown NPLs for ultrawide color gamut displays. Abstract : A high‐efficiency ultrapure green nanoplatelet light emitting diode is presented by minimizing the impact of nonradiative energy transfer issues in stacking nanoplatelet material. The external quantum efficiency and maximum luminance are enhanced to 2.16% and 22 400 cd m −2 . The color gamut can reach 104% Rec. 2020 color area by applying this device, exhibiting attraction for wide color gamut display.